Study on Status and Problem Research of Harmonic Gear Drive - Xiang Zhenlin; Li Ting; Yang Lin; Shang Yingrong (Jixie chuandong)
The development and application of harmonic gear drive in recent years are briefly reviewed，the development of gear tooth profile and the main factors affecting the life of reducer are mainly expounded. In the traditional tooth profile，the tooth profile has undergone the development stage from the linear tooth profile to the arc tooth profile，and then to the double arc tooth profile，the meshing characteristic and fatigue life at each stage are analyzed. The representative teeth of the current products are "S" tooth profile，"P" tooth profile，"δ" tooth profile and so on. In recent years，thin wall and long life are the focus of research，and a large number of researches focus on stress research of cylinder，gear tooth and wave generator. On this basis，suggestions are given on the research direction of harmonic reducer that should be paid attention to in the future，that is，the research of tooth profile，the analysis of material microstructure，the research of processing technology，the establishment of theoretical system，the problem of large natural frequency fluctuation，the accurate analysis and calculation of tooth meshing force，the influencing factors of transmission accuracy，etc.